Analisis space syntax pada transformasi rumah urban di Indonesia - Gierlang Bhakti Putra (ARTEKS : Jurnal Teknik Arsitektur, 2021)
Previous researches on urban housing transformation in Indonesia focused on the privacy and observable morphological changes of the house. This study aims to compare the spatial configuration between the original and transformed plan of the urban houses in Indonesia. Six houses in Jatiwaringin Asri, Bekasi were investigated as part of the case study. The original plan and transformed plan of the houses are obtained through the interviews with the occupants of the houses. The plans were analyzed graphically and mathematically using space syntax. The results show that the open plan space is central in both original and transformed plan. There is strong segregation between public and private area but the interior of the houses maintain low hierarchical organization.